Georges Sadoul rédacteur en chef de Mon Camarade (1933-1939). Un magazine illustré pour une culture de jeunesse communiste ? - Valérie Vignaux (Strenae, 2016)
Georges Sadoul (1904-1967), before becoming a film historian, was also one of the rare French specialists of children’s illustrated press during the interwar period. Author of several reference texts, from 1933 to 1939 he was the editor-in-chief of Mon Camarade, a periodical published by the Éditions sociales internationales directed by Léon Moussinac. Although financed by the French Communist Party, on the eve of the war this periodical benefitted from a significant number of readers and support from the Popular Front press. Sadoul was indeed committed to offering the youth an alternative to foreign or religious illustrated periodicals, by developing, among other things, a French school of comics. By studying the newspaper and the editorial choices made by Sadoul, we can analyze in detail the political comprehension of a youth culture during the interwar period.